FORMULASI & EVALUASI FISIK GRANUL EFFERVESCENT KOMBINASI EKSTRAK ETANOL 70% BUNGA ROSELLA (Hibiscus sabdariffa L.) & BUNGA TELANG (Clitoria ternatea L.) SEBAGAI ANTIOKSIDAN - Wahyudin Bin Jamaludin; Nadia Masytoh; Eka Fitri Susiani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Rosella (Hibiscus sabdariffa L.) and telang flower (Clitoria ternatea L.) contain anthocyanins which have antioxidant, so the researchers combined to use as effervescent granules. This study aims to determine the characteristics, and the antioxidant activity of effervescent granule combination of rosella and telang flower extract. Antioxidant activity testing using DPPH. The antioxidant activity of the combined thick extract was obtained ???????? 50 7.5 ppm, after that it was made into an effervescent granule preparation in 4 formulas. The resut show that all formulas had a characteristic taste of almost uniform color, dark turquoise. In all test formulas for water content, the results obtained are 1.68%-2.82%, compressibility index 11.641%-16%, angle of repose 31.2º-34.43º, flow time 6.25-6.83 seconds, dissolving time 208 -257 seconds and pH 6.2-6.6. The results of the antioxidant activity of effervescent granules revealed ???????? 50 of 62,628 ppm (strong).